2021
DOI: 10.3390/healthcare9121719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Regular Leisure-Time Physical Activity with Self-Reported Body Mass Index and Obesity Risk among Middle-Aged and Older Adults in Taiwan

Abstract: Through this study, we aimed to determine the association of regular leisure-time physical activity (LTPA) with self-reported body mass index (BMI) and obesity risk among middle-aged and older adults in Taiwan. We conducted a cross-sectional study and reviewed the data derived from the Taiwan National Physical Activity Survey (TNPAS). Responses from 12,687 participants aged 45–108 years from the database were collected in this study. All the participants completed a standardized structured questionnaire that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Management issues concerning individuals and organizations are integral to the research field of public health. By effectively utilizing health informatics techniques, valuable information can be extracted to provide deeper insights that support informed decision making [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: The Organization Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Management issues concerning individuals and organizations are integral to the research field of public health. By effectively utilizing health informatics techniques, valuable information can be extracted to provide deeper insights that support informed decision making [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: The Organization Of This Special Issuementioning
confidence: 99%
“…In the study by Chen et al [ 19 ], the association between regular leisure time physical activity (LTPA) and self-reported body mass index and obesity risk among middle-aged and older adults in Taiwan was examined using multiple linear regression and logistic regression. They found that regular LTPA was associated with the male gender, normal weight, excellent or good self-reported health status, and a lower rate of being underweight compared to nonregular LTPA.…”
Section: The Organization Of This Special Issuementioning
confidence: 99%
“…This study adopted a cross-sectional study design using nationally representative survey data on young adults aged 18-44 years from the National Physical Activity Survey (TNPAS) which was surveyed by the Sports Administration (SA), Ministry of Education in Taiwan. The respondents were recruited through random-digit dialing, and more detailed procedures have been discussed in other paragraphs [34,35]. The respondents include citizens who were older than 13 years old at the time the survey was conducted and strati ed by 22 cities/counties across Taiwan.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…However, higher grip strength is associated with lower waist circumference (WC; an indicator of central adiposity), after adjustment for BMI. A similar study indicated that relative grip strength was negatively associated with WC in young adults [19], and the use of properly adjusted confounding factors (e.g., age, education, occupation, and physical fitness) was necessary to prevent bias and distortion [20].…”
Section: Introductionmentioning
confidence: 98%